Counter-Terrorism in the Philippines: Review of Key Issues - Mendoza, Ronald U (Archīum Ateneo, 2020)
Last June 1, 2020, President Duterte certified the Anti-Terrorism Bill as urgent. Subsequently, Congress adopted the Senate version and passed it in the shortest time possible. The bill was intended to provide measures for the protection of the ordinary Filipino from acts of terrorism, and should have been with support and approval under normal circumstances. But this time is far from normal, and the bill has attracted opposition not only from the left, but from a broader sector of society.This brings us to these questions: what were the compelling reasons to certify the bill as more urgent than say, the extension of the extraordinary powers of the President to address the effects of the COVID-19 pandemic on the ordinary Filipino and our economy? Is the bill aligned with our constitution? Will it solve the domestic security problems festering for decades? What drives the objections against the bill? But perhaps the most disturbing concern among most members of society – do we have a common understanding of what is a terrorist?